De crime à criminalização de sua aversão: a prática sexual dissidente em discursos institucionais - Curtti-Gibin, Fernando (Universidade Federal de São Carlos, 2023)
This research, based on the theoretical-methodological assumptions of French Discourse Analysis, aims to analyze, discursively, institutional decisions made in Brazilian territory that refer to dissident sexual practices, in certain time frames. Specifically, the texts of institutional decisions, in general, judicial sentences will be worked, with the aim of developing an analysis of discourses on dissident sexual practices, constructed in different historical moments – from the dark ages in the Portuguese inquisition, when the inquisitorial process of the Court of the Holy Office considered sodomitic practices a sin-crime and, therefore, punishable with the death penalty; moving on to a time when the science dictated the rules of sexual practices and understood dissident practices as pathological, unhealthy; going through the Brazilian dictatorial repressions, when the conservative society and the military arbitrariness aimed at the moral control of “deviant” sexual behaviors, which were punished through arbitrary arrests and purges of public positions; until the most recent decision of 2019, contrary to the previous ones, handed down by the Federal Supreme Court, regarding the criminalization of the phobia directed to these practices. In this analysis, in the discursive field, especially from the theoretical-methodological postulates of Dominique Maingueneau and Alice Krieg-Planque, the dynamics raised in diverse and adverse conditions related to dissident sexual practices, in certain historical conjunctures, will be veryfied. This work is oriented not only to understand, discursively, how the various manifestations of the game of forces established by the repressive discourse to dissident sexual practices were constituted, but also to examine, from the analysis of the functioning of discourses that circulate – sometimes in a reproachful way, sometimes in a transgressive or liberating way – in these certain situations, the multiplicity of semantic dimensions, the enunciative values of action and transformation and the procedures of enunciative alterations that make up discrimination and prejudice in Brazilian society.
From crime to the criminalization of its aversion: the dissident sexual practice in institutional discourses
Du crime à la criminalisation de son aversion : la pratique sexuelle dissidente dans les discours institutionnels
Keywords: Criminalização; Discursos institucionais; Interincompreensão; Práticas sexuais dissidentes; Preconceito; Criminalization; Dissident sexual practices; Interincomprehension; Institutional discourses; Prejudice; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA